Quantum Computing and Cybersecurity: Navigating the Next Frontier of Digital Security - Bhooshan Ravikumar Gadkari (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the profound impact of quantum computing on cybersecurity, highlighting the potential threats to current cryptographic systems and the emerging solutions in the field of quantum-safe security. It begins by explaining the fundamental principles of quantum computing, contrasting them with classical computing, and detailing how quantum algorithms like Shor’s and Grover’s pose significant risks to widely used encryption methods such as RSA and AES. The article then delves into the development of post-quantum cryptography, discussing various approaches including lattice-based, code-based, and multivariate polynomial cryptography, with a focus on the NIST standardization initiative. Additionally, it examines quantum cryptography techniques, particularly Quantum Key Distribution (QKD), as alternative methods for secure communication. The article concludes by addressing the challenges organizations face in transitioning to quantum-safe security, including expertise gaps, resource limitations, and financial implications. It emphasizes the urgency of preparing for the quantum era while acknowledging the complexities involved in implementing quantum-resistant measures across global networks. This comprehensive overview provides insights into the evolving landscape of cybersecurity in the face of advancing quantum technologies and underscores the critical need for proactive strategies to safeguard digital infrastructure in the coming quantum age.